Sensitivity to Landscape Features: A Spatial Analysis of Field Geoscientists on the Move. Issue 3 (19th August 2016) - Baker, Kathleen M.; Petcovic, L. Heather
ABSTRACT: Intelligent behavior in everyday contexts may depend on both ability and an individual's disposition toward using that ability. Research into patterns of thinking has identified three logically distinct components necessary for dispositional behavior: ability, inclination, and sensitivity. Surprisingly, sensitivity appears to be the most common bottleneck to achieving quality outcomes. Using global positioning system data taken when field geologists ( n = 66) performed a bedrock mapping task, we assess sensitivity to landscape and its relationship to expertise, content knowledge in the discipline, thoroughness of route, and quality of outcome. A discipline-specific concept inventory served as a proxy measure for participant knowledge and ability. Thoroughness in the field served as an indicator of a participant's inclination to employ abilities critical to the success of the task. To assess sensitivity to opportunities in the landscape, we identified relatively small areas frequently visited by experienced geologists, then quantified the frequency with which participants across a continuum of mapping experience placed themselves in these areas. Results showed clear spatial differences in landscape use across scales by expertise level, suggesting that sensitivity to physical locations for quality thinking is less pronounced among inexperienced field geologists and correlates strongly with quality of outcome. These results are significant for the education of field researchers because cultivation of sensitivity to opportunities in the landscape for higher-quality thinking presents a different sort of instructional challenge than that of directly teaching discipline specific content or traditional mapping skills.